PGENERATION Z COMMUNICATION EXPERIENCE AT MOJA TOURIST DESTINATION - Priyansa Utami, Fina; Imaddudin, (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
As a thematic tourist attraction, MoJa presents a unique concept to create a different experience for visitors. Visitor experience is the main source of visitor confidence to visit again or recommend the tourist attraction to other people. This research aims to identify because of motive and in order to motive in Generation Z's communication experience at the MoJa Tourism Destination. The phenomenological qualitative research method was chosen to understand the research situation in more detail. Research data was collected through observations, documents and semistructured and open-ended interviews regarding the communication experiences of Generation Z visitors at the MoJa tourist destination. Based on the results of interviews with informants, it was found that the motives that influenced Generation Z's communication experience in visiting MoJa were a unique and different experience, social attraction, easy accessibility and the influence of social media. Meanwhile, in order to motive, the goal of Generation Z's communication experience for visiting MoJa is because they want to visit MoJa to enjoy time with the people closest to them, such as a partner to date and spend vacation time with friends. MoJa can continue to innovate by holding events that allow visitors to interact with each other, increase accessibility, and add facilities that are unique and attract the interest of Generation Z.